2018
DOI: 10.1002/jso.24977
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection is associated with favorable outcome in advanced gastric cancer patients treated with S‐1 adjuvant chemotherapy

Abstract: The favorable outcome of H. pylori-positive patients implies that the host immune system is modulated by H. pylori enhancing the chemotherapeutic efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 43 publications
(111 reference statements)
0
35
0
Order By: Relevance
“…Infection with Helicobacter pylori ( H. pylori ), a bacterial carcinogen, contributed to ~75% of the global gastric cancer burden and its eradication therapy during early stages of the precancerous cascade can prevent gastric cancer development 2 . Recently, a multicenter study further confirmed that post-operative S-1 (oral fluoropyrimidine comprised of tegafur, gimeracil, and oteracil) adjuvant chemotherapy led to an increase in both overall survival and disease-free survival in H. pylori -positive advanced gastric cancer patients than H. pylori -negative patients 3 . Thus, unveiling the precise mechanisms that regulate cancer development in response to H. pylori infection is urgently required for improving the prognosis of gastric cancer patients.…”
Section: Introductionmentioning
confidence: 91%
“…Infection with Helicobacter pylori ( H. pylori ), a bacterial carcinogen, contributed to ~75% of the global gastric cancer burden and its eradication therapy during early stages of the precancerous cascade can prevent gastric cancer development 2 . Recently, a multicenter study further confirmed that post-operative S-1 (oral fluoropyrimidine comprised of tegafur, gimeracil, and oteracil) adjuvant chemotherapy led to an increase in both overall survival and disease-free survival in H. pylori -positive advanced gastric cancer patients than H. pylori -negative patients 3 . Thus, unveiling the precise mechanisms that regulate cancer development in response to H. pylori infection is urgently required for improving the prognosis of gastric cancer patients.…”
Section: Introductionmentioning
confidence: 91%
“…These results suggested that the TP53 codon 72 polymorphisms could be a useful index to assess the efficacy of postoperative adjuvant chemotherapy using S‐1, an oral fluoropyrimidine . However, the TP53 codon 72 polymorphism did not appear to be a strong biomarker for predicting S‐1 efficacy in surgery alone and S‐1 treated stage II/III patients with gastric cancer, suggesting that 5‐FU sensitivity in gastric cancer cell lines may not exclusively depend on a TP53 codon 72 polymorphism . We then hypothesized that the TP53 genotype might have simply reflected the degree of biological malignancy.…”
Section: Discussionmentioning
confidence: 98%
“…The study included 658 patients who underwent gastrectomy with curative intent (R0 surgery) from October 2000 to November 2009 followed by survival outcome survey until April 2014. The patients were histologically diagnosed as primary adenocarcinoma of the stomach and enrolled in the Northern Japan Gastric Cancer Study Consortium (NCT 01905969) . Formalin fixed paraffin embedded (FFPE) tissue samples and corresponding patient information were collected.…”
Section: Methodsmentioning
confidence: 99%
“…[26,27] However, Nishizuka et al reported that H. pyloriinfected patients had superior survival rates when treated with adjuvant S-1, which was compatible with our results. [28] Host antitumor immunity may be enhanced by H. pylori infection and uoropyrimidine-mediated eradication of myeloid-derived suppressor cells, which may contribute to a survival advantage. [29] Furthermore, we noticed that the survival outcomes in stage IB-IIIA or N0-1 disease were better with S-1, whereas platinum-based doublets led to additional bene ts in the more advanced diseases.…”
Section: Factors Associated With Adjuvant S-1mentioning
confidence: 99%